Implementation of multidimensional knowledge translation strategies to improve procedural pain in hospitalized children - Stevens, Bonnie J; Yamada, Janet; Promislow, Sara; Stinson, Jennifer; Harrison, Denise; Victor, J C (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Despite extensive research, institutional policies, and practice guidelines, procedural pain remains undertreated in hospitalized children. Knowledge translation (KT) strategies have been employed to bridge the research to practice gap with varying success. The most effective single or combination of KT strategies has not been found. A multifaceted KT intervention, Evidence-based Practice for Improving Quality (EPIQ), that included tailored KT strategies was effective in improving pain practices and clinical outcomes at the unit level in a prospective comparative cohort study in 32 hospital units (16 EPIQ intervention and 16 Standard Care), in eight pediatric hospitals in Canada. In a study of the 16 EPIQ units (two at each hospital) only, the objectives were to: determine the effectiveness of evidence-based KT strategies implemented to achieve unit aims; describe the KT strategies implemented and their influence on pain assessment and management across unit types; and identify facilitators and barriers to their implementation. Methods Data were collected from each EPIQ intervention unit on targeted pain practices and KT strategies implemented, through chart review and a process evaluation checklist, following four intervention cycles over a 15-month period. Results Following the completion of the four cycle intervention, 78% of 23 targeted pain practice aims across units were achieved within 80% of the stated aims. A statistically significant improvement was found in the proportion of children receiving pain assessment and management, regardless of pre-determined aims (p < 0.001). The median number of KT strategies implemented was 35 and included reminders, educational outreach and materials, and audit and feedback. Units successful in achieving their aims implemented more KT strategies than units that did not. No specific type of single or combination of KT strategies was more effective in improving pain assessment and management outcomes. Tailoring KT strategies to unit context, support from unit leadership, staff engagement, and dedicated time and resources were identified as facilitating effective implementation of the strategies. Conclusions Further research is required to better understand implementation outcomes, such as feasibility and fidelity, how context influences the effectiveness of multifaceted KT strategies, and the sustainability of improved pain practices and outcomes over time.